The antifouling performance of an ultrafiltration membrane with pre-deposited carbon nanofiber layers for water treatment - Liu,T; Zhou,H; Graham,N; Lian,Y; Yu,W; Sun,K (Journal of Membrane Science, 2018)
In order to improve the performance of the ultrafiltration (UF) membrane process in drinking water treatment, in terms of permeate flux and natural organic matter (NOM) removal, a new form of carbon nanofiber (CNF) layer derived from bacterial cellulose (BC) was prepared and applied as a pre-deposited coating on the UF membrane surface. Using bench-scale, dead-end filtration tests, both CNF and CNF modified by ethanol treatment (M-CNF), were evaluated for the treatment of two model NOM solutions, namely bovine serum albumin (BSA) and sodium alginate (SA). The results showed that both types of coating were effective in mitigating membrane fouling (lower flux decline), with the mitigation increasing with the coating quantity, and also enhanced the removal of BSA and SA. In particular, the M-CNF layer at the greater loading (24g/m2) was able to reduce membrane fouling to a very substantial degree and achieve >90% removal of BSA and SA. Characterization of the CNF and M-CNF layers showed significant differences in their morphological and structural properties which may explain the observed differences in their ability to reduce membrane fouling; protection of the UF membrane by the carbon nanofiber layers may be attributed to both physical separation and surface adsorption of the NOM biopolymers.